Religious preoccupation and its relationship to emotional equilibrium among university students - Kuwayta, Kadhem Mohsen (Al-Adab Journal, 2015)
The research aims to identify the preoccupation Aladena and also to identify the balance of emotional and what is their relationship with the university students, and for the purpose of verifying that the use of religious preoccupation prepared by al-Obeidi Scale (2010) and building balance the emotional scale according to the adopted theoretical framework as the number of paragraphs of religious preoccupation scale (19) items and scale poise emotional (30) paragraph has been confirmed Alsekoumtrah characteristics of the two measures and then was applied tools to the research sample, which amounted to (300) students from the university students were selected random stratified way, and the results showed that the sample individuals with religious preoccupation They have poise emotional as the average grades higher than the central premise, as well as the presence of correlation positive between religious preoccupation and balance the emotional relationship, and the reason is that religion is necessary, especially in our society in order to psychological integration as integration of thinking and a sense of organization in ways operations, and consistent aims to achieve health objectives, and reasonable, and in turn leads to poise emotional when the student is assisted to perform mental functions system and format, and it paves the way for making the mind can control freaks, and rein in the self, and the reduction of Httha, and this is what makes the student predisposed to work and active thinking, and more accepted by the community, and more successful in influencing them, and increases the ability to establish successful relationships